POSTCOLONIAL IRONY. THE LANGUAGE OF POLITICAL CORRECTNESS AS A SOURCE OF POLISH LITERARY FICTION AFTER 1989 - Kledzik, Emilia (Porównania, 2014)
The article argues that Polish post-1989 literature absorbed the language of numerous debates on controversial issues that have been present in the Polish public opinion for twenty-five years of democracy – including the phenomenon of the socalled “political correctness”. The basic rhetorical figure used in its defense by three writers – Mariusz Sieniewicz, Arthur Daniel Liskowacki and Joanna Bator – is an ironic quotation of hate speech. The author compares this phenomenon to the classic figure of post-colonial mimicry. In this case, the ethnocentric language of the communist regime would constitute the language of the colonizer. Literature, whose main character is the language of exclusion, provides a good study of how it helps constructing and dismantling the identity.